Research Status and Prospect of Femtosecond Laser Shock Peening Technology - WANG Zongshen, ZANG Tong, CHEN Lei, KONG Meng, ZHENG Hongyu (Cailiao Baohu, 2023)
As a micro-scale surface strengthening technique，femtosecond laser shock peening has the advantages of low thermal effect，shallow impact depth， high energy efficiency and process flexibility， which makes its great application advantages in surface modification of micro structures with complicated shapes， surface micro shaping of macro components and micro shock forming.Herein the development history of femtosecond laser shock peening technology was summarized， and the influence rules and mechanisms of impact mode， laser parameters，additional energy fields and other factors on the strengthening effect were summarized.Moreover， the potential applications and development trends of femtosecond laser shock peening technology were prospected， which could provide necessary guidance and support to break through the key issues of femtosecond laser shock peening and promote the industrial application of technology.